A hydroxamic-acid-containing nucleoside inhibits DNA repair nuclease SNM1A - Doherty, W; Dürr, E; Baddock, H; Lee, S; McHugh, P; Brown, T; Senge, M; Scanlan, E; McGouran, J (Royal Society of Chemistry, 2019)
Nine modified nucleosides, incorporating zinc-binding pharmacophores, have been synthesised and evaluated as inhibitors of the DNA repair nuclease SNM1A. The series included oxyamides, hydroxamic acids, hydroxamates, a hydrazide, a squarate ester and a squaramide. A hydroxamic acid-derived nucleoside inhibited the enzyme, offering a novel approach for potential therapeutic development through the use of rationally designed nucleoside derived inhibitors.